Gang Affiliation and Radicalization to Violent Extremism within Somali-American Communities, 5 North American Cities, 2013-2019 - Ellis, Heidi ([Verlag nicht ermittelbar], 2020)
How is the process of radicalization understood over time? Do current radicalization to violence differ from earlier waves? How can these understandings be utilized to prevent radicalization to violence and--equally important--understand the reach and impact of programs designed to do so? The overall goal of this project was to pursue the following aims: Aim 1: To understand how adversity and social bonds relate to changes in openness to violent extremism over time. Aim 2: To evaluate experience and perception of, and the effectiveness of, Countering Violent Extremism (CVE) activities. Aim 3: To evaluate mechanisms of change in violent extremism. Aim 4: To understand similarities/ differences in experiences and/or histories of Somali youth who joined Al-Shabab vs. those known to have been killed in Syria, fighting with ISIS and other terrorist groups. The above aims were accomplished through extending an ongoing longitudinal research program to span 5 years, and expanding a psychological autopsy sample to include Somali youth who have left Minneapolis and been killed fighting with ISIS and other terrorist groups in Syria. Data collection for the longitudinal study consisted of conducting an additional wave of structured interviews with Somali youth (between the ages of 21-33); interviews included assessments of structural adversity (resettlement hardships, trauma exposure, and discrimination), social factors (connection to the resettlement community and/or Somali diaspora community, internet use, and level of acculturation) delinquency, gang involvement, civic engagement, and support for legal and illegal (violent) actions in support of political change. The researchers used latent transition analysis (LTA), generalized estimating equation modeling, and linear regression modeling to accomplish Aims 1-3. Aim 4 was accomplished by using a combination of open source data analysis, psychological autopsy and case analysis methodology. The researchers expanded our current in-depth case studies of Somali youth who left Minneapolis to join al-Shabaab (N = 23, males aged 22-30) to include those who joined ISIS or Al-Nusra (N=4, males aged 18-29). Research questions associated with Aim 4 were analyzed using a psychological autopsy method of developing case histories. Case histories were coded for themes and analyzed for convergence or divergence with case histories of youth who joined Al-Shabab. Scholarly products include manuscripts in journals relevant to criminal justice, policy briefs, and interim and final reports. This project builds on partnerships between Boston Children's Hospital, Somali communities, and Georgia State University.